Extratos vegetais e produtos comerciais no controle de Diplocarpon rosae e na indução de resistência em roseiras - Simon, Janaina Miyashiro (2016)
The objective of this study was to evaluate the potential of extracts derived from medicinal plants (Rosmarinus officinalis, Equisetum arvense and Moringa oleifera) and commercial products (based on plant extracts, vegetable oils and potassium phosphite) in vitro control and greenhouse of Diplocarpon rosae and evaluate through resistance induction of determining the specific activity of oxidative enzymes, catalase and polyphenol in phytopathogen and roses. In vitro evaluated the effect of treatments on the pathogen by mycelial growth rate index, inhibition of mycelial growth inhibition of sporulation, sporulation rate, protein synthesis, peroxidase and catalase specific activity using aqueous crude extract (ACE) to R. officinalis leaves (1%); ACE E. arvense stem (1%); ACE M. oleifera seeds (1%); commercial product based on fermented plant extracts (0.01%); commercial product based on potassium phosphite (0.01%); commercial product based on vegetable oils (0.01%); Ecolife® (0.01%); Thiophanate methyl fungicide basis (0.007%); adjuvant (0.0025%) on potato dextrose agar (PDA) and potato dextrose (BD). Under greenhouse conditions were evaluated incidence and severity of disease black spot, productivity (number of buttons), biometrics (length buttons, length and stem thickness), chlorophyll content and peroxidase, catalase and polyphenol oxidase specific activity, using the same treatments with ten times higher doses and the control was distilled water. In vitro results with commercial product based on vegetable oils 56% reduced mycelial growth; ACE E. arvense and commercial product based on fermented plant extracts inhibited 81 and 75% sporulation. The treatments with ACE R. officinalis, E. arvense, M. oleifera, commercial product based on vegetable oils and Ecolife® increased protein synthesis in D.rosae mycelium. Also in the mycelium was increased specific activity of peroxidase and catalase in ACE R. officinalis and commercial product based on potassium phosphite, respectively. In a greenhouse the largest stem length was observed in the treatment with the commercial product based on potassium phosphite and the greatest thickness of the stem in the three commercial products. The highest enzyme activities were observed in the peroxidase enzyme with a commercial product based on potassium phosphite in the first application, catalase, ACE M. oleifera and potassium phosphite on first application and polyphenol with ACE R. officinalis and M. oleifera in the third application. Natural products can be used in disease control blight and resistance induction, showing promising results.